2022
DOI: 10.3390/d14010057
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Recommendations for Establishing Threshold Values for the NIS Trend Indicator in the Mediterranean Sea

Abstract: In the present work, we analysed time series data on the introduction of new non-indigenous species (NIS) in the Mediterranean between 1970 and 2017, aiming to arrive at recommendations concerning the reference period and provisional threshold values for the NIS trend indicator. We employed regression analysis and breakpoint structural analysis. Our results confirm earlier findings that the reference conditions differ for the four Mediterranean subregions, and support a shortening of the reporting cycle from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…However, spatial information at the necessary grain would need to be collated and made available to calculate a spatially explicit pathway indicator of this type. Progress collating data on a standard suite of invasion pathways used across invasive alien taxa (Harrower et al., 2018), in addition to the incorporation of pathway information in Darwin Core (Groom et al., 2019), are steps toward future development and adoption of an invasion pathways indicator (Faulkner et al., 2020; Galanidi & Zenetos, 2022; McGrannachan et al., 2021; Pergl et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, spatial information at the necessary grain would need to be collated and made available to calculate a spatially explicit pathway indicator of this type. Progress collating data on a standard suite of invasion pathways used across invasive alien taxa (Harrower et al., 2018), in addition to the incorporation of pathway information in Darwin Core (Groom et al., 2019), are steps toward future development and adoption of an invasion pathways indicator (Faulkner et al., 2020; Galanidi & Zenetos, 2022; McGrannachan et al., 2021; Pergl et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the Mediterranean, interdisciplinary scientific initiatives have attempted to disentangle the phenomenon of marine invasions either through the ecological investigation of species’ dispersal and the responses of NIS in native communities 20 , the integration of species’ traits to interpret NIS successive expansion 21 , 22 , or by employing a time series approach to explore the rate of introductions 23 . In the last decade, an additional novel approach has emerged by using advanced ecological models to project the distribution of NIS in the near future (i.e., Species Distribution Models—SDMs) based on predicted environmental thresholds 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The eastern Mediterranean Sea is currently witnessing an unprecedented invasion by alien marine species, introduced mainly from the Red Sea via the Suez Canal, various oceans via ships (hull fouling or ballast water) and mariculture (Zenetos et al, 2012;Galanidi et al, 2023). Twenty-three isopod alien species occur in the Mediterranean Sea (Castelló et al, 2020), but only two of them have been reported in the surveys conducted so far on the Turkish coasts (Paradella dianae (Menzies, 1962), Sphaeroma walkeri Stebbing, 1905(Bakır et al, 2014, whereas a third one [Paracerceis sculpta (Holmes, 1904)] has been found only on boat hulls (Ulman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%